To Ban or Not to Ban? : Regulating Dual Practice in Palestine - Alaref, Jumana; Awwad, Jawad; Araujo, Edson; Lemier, Christophe; Hillis, Samira Ahmed; Ozaltin, Emre (Taylor and Francis, 2017)
Dual practice, health professionals working simultaneously in the public and private sectors, is perceived to negatively impact quality of health care. Though a range of policy options exists to regulate dual practice, little is known about the impact of different options on quality of care. Successful policy is dependent on a country's health care system, health labor market, monitoring of private sector activity, and enforceability of regulations. This article provides evidence on the potential impact of banning dual practice in Palestine. We apply theoretical evidence and international experience, together with context-specific primary and secondary data, to assess the policy's enforceability, implications, and sustainability in the Palestinian context. In this setting, though the risk of losing health workers to the private sector is low, banning dual practice will most likely lead to the “brain drain” of rare specialists from the public sector. Moreover, though there is some evidence that dual practice is negatively impacting quality of care, poor quality in public facilities associated with shortages in supplies and equipment, poor organizational and management practices, low motivation, and absence of monitoring and accountability systems are unlikely to change by banning dual practice. Finally, the ban, as conceptualized, is fiscally unsustainable in a strained health budget and may be challenging to enforce due to a weak monitoring system. Overall, it was found that an outright ban on dual practice would not reduce the financial burden on patients and enhance their access to quality services in the public sector.